The Skin as a Diagnostic Anchor: Complete Mucocutaneous Phenotype of Neurofibromatosis Type 1 in A Young Adult with Severe Dystrophic Cervical Kyphosis - Ana Sophia Ortiz Robles; Flavio Antonio Sarabia Alba; Francisco Alejandro Sarabia Alba (International Journal of Medical Science and Clinical Research Studies, 2026)
Neurofibromatosis type 1 (NF1) is an autosomal dominant tumor-predisposition syndrome caused by pathogenic variants in the NF1 gene and characterized by significant phenotypic variability. Pigmentary and cutaneous lesions, such as café-au-lait macules, skinfold freckling, and dermal or plexiform neurofibromas, occur in nearly all affected individuals and form the core diagnostic criteria. These features often provide the earliest indication of NF1 before neurological, skeletal, or ophthalmological complications. Complete cutaneous phenotypes are less frequently documented when extracutaneous manifestations predominate, and pigmentary-pilar markers of subclinical internal disease are often overlooked. A 20-year-old man was evaluated after experiencing four years of progressive axial cervical pain following a motorcycle accident, accompanied by radicular pain and gait disturbance that necessitated wheelchair use. Imaging revealed severe destruction of the C5-C6 vertebral bodies with kyphotic deformity, subsequently identified as compressive myelopathy secondary to NF1. Skeletal and surgical findings are reported separately. The patient's father, two paternal aunts, and paternal grandmother exhibited cutaneous lesions consistent with neurofibromas across three generations, supporting autosomal dominant inheritance. Independent of the skeletal assessment, a systematic mucocutaneous examination identified multiple café-au-lait macules on the trunk, axilla, thigh, and leg; bilateral axillary and inguinal freckling extending atypically to the neck and palmoplantar surfaces; and hyperpigmented, hypertrichotic patches on the right arm and left hand. The family reported a dorsal patch with hypertrichosis that could not be examined due to cervical immobilization. The patient fulfilled four of the seven revised 2021 NF1 criteria (≥6 café-au-lait macules, axillary/inguinal freckling, ≥2 cutaneous neurofibromas, and an affected first-degree relative), exceeding the two required for diagnosis. Although a multigenerational cutaneous phenotype was present, the diagnosis was established only after four years of orthopedic and neurological symptoms. This case illustrates how systemic complications of NF1 can delay recognition of a diagnosis that could have been identified earlier through a structured skin examination. Freckling extending beyond the classic axillary and inguinal distribution to the neck and palmoplantar surfaces warrants further characterization. Hyperpigmentation and hypertrichosis overlying the skin are recognized markers of underlying plexiform neurofibroma, which often remains occult and carries a lifelong risk of malignant transformation. In this patient, imaging did not confirm these markers, and targeted MRI of the affected limbs is recommended next. The unexamined dorsal lesion and the three-generation pedigree further inform follow-up priorities and genetic counseling. The complete mucocutaneous phenotype in this patient was sufficient to establish the diagnosis of NF1, despite the initial presentation with a rare and severe skeletal complication. This case underscores the importance of systematic skin examination and suggests that pigmentary-pilar markers may indicate clinically silent internal disease.